CFD Simulations of Marine Hydrodynamics - Demirel, Yigit Kemal (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
CFD is an emerging area and is gaining popularity due to the availability of ever-increasing computational power. If used accurately, CFD methods may overcome the limitations of experimental and other numerical methods, in some respects. This Special Issue focuses on Computational Fluid Dynamics (CFD) Simulations of Marine Hydrodynamics with a specific focus on the applications of naval architecture and ocean engineering, and it comprises 24 original articles that advance state-of-the-art CFD applications in marine hydrodynamics and/or review the progress and future directions of research in this field. The published articles cover a wide range of subjects relevant to naval architecture and ocean engineering, including but not limited to; ship resistance and propulsion, seakeeping and maneuverability, hydrodynamics of marine renewable energy devices, validation and verification of computational fluid dynamics (CFD), EFD/CFD combined methods, fouling/coating hydrodynamics.